Oor die teologiese inhoud van die Belydenis van Belhar - D. J. Smit (Acta Theologica)
The essay argues that the theological content is indeed the most important contribution of Reformed confessional documents, but that the theological content can only be understood against the specific historical, which most often means socio-political, circumstances in which these confessions were originally adopted. Regarding the Confession of Belhar, the theological content consists in three confessional claims (each including allusions to the false teaching that is implicitly thereby unmasked and rejected) within the broader framework of an introduction and conclusion, involving key theological claims as well, respectively about the nature of the church and the lordship of Jesus Christ. After some interpretive comments on all five of these structural aspects – the introduction and conclusion and the three claims – brief consideration is given to the nature of reception of confessional documents in the Reformed tradition and some implications for the reception of the theological content of the Confession of Belhar.